2021
DOI: 10.4081/ija.2021.1780
|View full text |Cite
|
Sign up to set email alerts
|

Site- and time-specific early weed control is able to reduce herbicide use in maize - a case study

Abstract: Highlights- Efficacy of UAVs and emergence predictive models for weed control has been confirmed. - Combination of time-specific and site-specific weed control provides optimal results.- Use of timely prescription maps can substantially reduce herbicide use.   Remote sensing using unmanned aerial vehicles (UAVs) for weed detection is a valuable asset in agriculture and is vastly used for site-specific weed control. Alongside site-specific methods, time-specific weed control is another critical aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…Norsworthy and Oliveira identify the best time during the development of Zea mais to monitor weed growth [ 57 ]. Finally, other authors propose some strategies to be adopted to protect the yield of corn crops in the presence of weeds [ 58 , 59 ]. All these data confirm the need to better understand the biological systems involved in the interaction between the multiple species of weeds and crops of agronomic value.…”
Section: Discussionmentioning
confidence: 99%
“…Norsworthy and Oliveira identify the best time during the development of Zea mais to monitor weed growth [ 57 ]. Finally, other authors propose some strategies to be adopted to protect the yield of corn crops in the presence of weeds [ 58 , 59 ]. All these data confirm the need to better understand the biological systems involved in the interaction between the multiple species of weeds and crops of agronomic value.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating both decision support systems can address the problem of ununiformed weed populations in time and space, 5,45 thereby maximizing the efficacy of mechanical or chemical weed control methods and reducing costs. A recent study conducted in Italy following this hypothesis reported promising results in herbicide and cost reduction 46 …”
Section: Resultsmentioning
confidence: 93%
“…A recent study conducted in Italy following this hypothesis reported promising results in herbicide and cost reduction. 46…”
Section: Utility As Decision Support Systemmentioning
confidence: 99%
“…ANN also being used differentiate between weed, crop, and soil. When compared between ANN and visible atmospherically resistant index (VARI), ANN has higher accuracy of 98.6% and Cohen's Kappa value of k = 83.7 compared to VARI which is 98.1% and k = 72, respectively [81]. However, higher reduction percentage of the sprayed herbicide area that ranged from 65.29% to 93.35% when VARI was used, and from 42.43% to 87.82% when ANN was used.…”
Section: Algorithms and Classification Techniques For Weed Mappingmentioning
confidence: 99%
“…With the small UAVs, such as Phantom 3 Professional (Da-Jiang Innovations, Shenzhen, China) quadrotor, it is possible to map 10 ha in 20 min at 40 m flight altitude, which corresponds to the duration of one battery [74]. The best date for a weed emergence prediction model survey was implemented using a UAV with visible range sensors, resulting in an orthophoto with a spectral resolution of 3 cm, allowing for good weed detection [81].…”
Section: Effect Of Spatial and Spectral Resolutions On Weed Detectionmentioning
confidence: 99%